'AND'-based fluorescence scaffold for the detection of ROS/RNS and a second analyte. Issue 61 (12th July 2018) - Odyniec, Maria L.; Sedgwick, Adam C.; Swan, Alexander H.; Weber, Maria; Tang, T. M. Simon; Gardiner, Jordan E.; Zhang, Miao; Jiang, Yun-Bao; Kociok-Kohn, Gabriele; Elmes, Robert B. P.; Bull, Steven D.; He, Xiao-Peng; et al.
Abstract : A novel fluorescence-based scaffold was developed enabling the production of 'AND' based fluorescence probes – ROS/RNS and a second analyte. Abstract : Traditionally, fluorescence probes have focused on the detection of a single biomarker for a specific process. In this work, we set out to develop a number of fluorescence probes that enable the detection of a chosen analyte in the presence of reactive oxygen/nitrogen species (ROS/RNS). These fluorescence probes when activated result in the formation of the highly fluorescent pink dye, resorufin. Therefore, we have labelled these fluorescent probes as 'Pinkments'. Our first 'Pinkment' was shown to detect biologically relevant concentrations of ONOO − and have an excellent selectivity against other ROS/RNS.Pinkment-OH was developed to provide a core unit which could be easily functionalised to produce a range of 'AND' based fluorescence probes for the detection of ROS/RNS and a second analyte. For proof of concept, we synthesisedPinkment-OTBS andPinkment-OAc . These 'AND'-based probes were successfully shown to detect ROS/RNS and F − or esterase, respectively.